2016
DOI: 10.1016/j.cgh.2015.11.007
|View full text |Cite
|
Sign up to set email alerts
|

In Patients With Cirrhosis, Driving Simulator Performance Is Associated With Real-life Driving

Abstract: Background & Aims Minimal hepatic encephalopathy (MHE) has been linked to higher real-life rates of automobile crashes and poor performance in driving simulation studies, but the link between driving simulator performance and real-life automobile crashes has not been clearly established. Further, not all patients with MHE are unsafe drivers, but it is unclear how to distinguish them from unsafe drivers. We investigated the link between performance on driving simulators and real-life automobile accidents and tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 22 publications
0
21
0
1
Order By: Relevance
“…Paper- pencil tests for MHE diagnosis (48% of patients), driving simulation was completed by 163 patients, driving records were collected from the Virginia department of motor vehicles (DMV) and self-reported by patients at the study entry, also questions about alcohol usage/cessation was recorded[64]. Using the DMV records and comparing those to the simulation results the drivers were classified as either safe or unsafe.…”
Section: Linking Che Simulation and Traffic Offensesmentioning
confidence: 99%
See 4 more Smart Citations
“…Paper- pencil tests for MHE diagnosis (48% of patients), driving simulation was completed by 163 patients, driving records were collected from the Virginia department of motor vehicles (DMV) and self-reported by patients at the study entry, also questions about alcohol usage/cessation was recorded[64]. Using the DMV records and comparing those to the simulation results the drivers were classified as either safe or unsafe.…”
Section: Linking Che Simulation and Traffic Offensesmentioning
confidence: 99%
“…On regression analysis, it was found that in MHE patients with recent alcohol cessation (less than a year) having illegal turns during simulator navigation tasks were associated with real-life automobile crashes. The authors concluded, “ Traffic safety counseling should focus on patients with cirrhosis who recently quit consuming alcohol and perform poorly on driving simulation[64]. ” In the discussion following these results, the authors write that these impaired simulator and real-life traffic outcomes are stable even when followed after a year.…”
Section: Linking Che Simulation and Traffic Offensesmentioning
confidence: 99%
See 3 more Smart Citations